Role of Politics and Government in Digital Age - Thanh Nguyen, Phong; Umasih, Umasih; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang; Shankar, K. (Opción, 2019)
The Internet has changed political conduct, from campaigning and voting for policy change, to dissent and even revolution. This represents a test to states, as political developments become progressively violent, flighty, and social orders harder to govern. To comprehend this drastically changed political world, we are reconsidering the models and theoretical structures of political theory and hypothesis, and creating social information science techniques to comprehend political conduct.